Basic principles for the management of neurological patients during the COVID-19 pandemic - S. V. Kopishinskaya; N. O. Zharinova; I. A. Velichko; N. G. Zhukova; V. V. Bucev; I. V. Korobejnikov; A. A. Gasanova; A. S. Arakelyan; O. V. Petruchik; A. N. Payudis (Нервно-мышечные болезни)
In a COVID-19 pandemic, a neurologist needs to be able to assess the risks of virus infection in patients with individual neurological diseases. The review presents categories of risk groups from the Association of British Neurologists for neuromuscular diseases, multiple sclerosis and other autoimmune diseases of the central nervous system, stroke, epilepsy and Parkinson’s disease. The risk of infection and the management of patients with neuromuscular diseases are analyzed in detail. The use of multiple sclerosis disease modifying drugs, the treatment of stroke patients are discussed. The data from the international guidelines for the management of patients with epilepsy and Parkinson’s disease are presented.